Mapping The Principal-Agent Relation In Social Media: A Data Mining Approach - Ujang Fahmi; Canggih Puspo Puspo Wibowo; Faturahman Yudanto Yudanto (Jurnal Administrasi dan Kebijakan Publik, 2018)
Most of the research on social media is conducted to comprehend and to exploit the presence of public opinion in it. Meanwhile, there has been limited research that explores the engagement process and interaction results from social media accounts. Therefore, this study aims to map the interaction between government and society in social media in principal-agent context. Exploration made from tweets posted by @KemenDesa and citizens' tweets which are mentioning @KemenDesa dated from 1 October 2014 to 31 September 2017. The results give an idea of the engagement process and the content of the interaction so that the relationship between them in the principal-agent context can be mapped. In addition, the results of the analysis can also be used to evaluate the use of social media by public organizations and communities as an alternative medium to communicate.